PEMANFAATAN DIGITAL MARKETING UNTUK PENINGKATAN DAYA SAING EKONOMI PESANTREN DAARUL AZMI - Irfan Rizka Akbar; Fajar Yanuar Ishak; Dimas Indra Wahyudi; Adam Kurniawan (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The Student Creativity Program (PKM) was carried out at Pesantren Daarul Azmi with a focus on applying digital marketing strategies to strengthen the institution's image, visibility, and outreach, as a foundation for enhancing its economic competitiveness. Pesantren Daarul Azmi actively organizes religious activities such as Qur'an study sessions, tahfidz and tilawah competitions, and student character development, yet these activities had not been optimally documented or promoted online, limiting the pesantren's recognition and its capacity to build economic value from public engagement. This PKM activity aimed to provide basic training in digital literacy, social media management, creative content creation, and digital communication strategy for students and pesantren administrators.The implementation method used a community-based learning approach consisting of needs observation, content management training (photo, video, and text), and mentoring for managing the pesantren's official social media accounts such as TikTok. The results show a significant improvement in participants' ability to create and manage publication content; approximately 78% of participants were able to design informative and appealing posts that positively represent the pesantren's activities. This is reflected in the growth of the pesantren's social media following and increased digital public engagement with its religious activities. Through this program, the pesantren is expected not only to remain a traditional Islamic education center, but also to leverage digital technology to strengthen its da'wah and economic competitiveness in the modern era.